Readiness of Application of Electronic Medical Records in Bethesda Lempuyangwangi Hospital, Yogyakarta - Pradnyantara, I Gusti Agung Ngurah Putra; Murti, Bhisma; Tamtomo, Didik (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Based on the strategic plan of the Ministry of Health of the Republic of Indonesia for 20202024, all hospitals can gradually implement electronic medical records. However, there are still many obstacles experienced by hospitals in implementing Electronic Medical Record (EMR), readiness assessments can be used to determine readiness, indications and requirements in facilitating the implementation of EMR so as to avoid various obstacles during the implementation process.Subjects and Method: This was a qualitative descriptive study with a case study design. The study was conducted at Bethesda Lempuyangwangi Hospital, Yogyakarta, from May to June 2022. The data collected was the readiness to implement EMR in terms of organizational alignment and management capacity, by conducting indepth interviews with 7 people. The study subjects were determined by purposive sampling who were considered to have the capacity to make decisions related to EMR.Results: Bethesda Lempuyangwangi Hospital in implementing EMR from organizational alignment is said to be ready, the board of directors has known and understood that the implementation of RME has many benefits, the organization has been planned and the unit leadership understands the implementation risk in case of failure, to anticipate this, a longterm vision has been prepared. Readiness to implement EMR from management capacity can be improved because the IT committee has not yet been formed consisting of stakeholder representatives and hospitals, organization is still within the scope of the hospital, where ICT has been included in the organization's strategic plan. The roles and responsibilities for EMR implementation are defined with clear accountability to vendors and have been documented, the board of directors has considered planning the EMR implementation budget, funding for ongoing clinical IT adoption and the required standards are included in future planning and will be part of the IT budget.Conclusion: Bethesda Lempuyangwangi Hospital is ready to implement electronic medical records that will be applied to inpatient units, this can be seen from the alignment of the organization and management capacity where the culture, organization, leadership, strategy, information management, clinical staff, accountability and budget finance have been planned and have started held.Keywords: Readiness, Electronic Medical RecordCorrespondence: I Gusti Agung Ngurah Putra Pradnyantara. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: gustipradnyantara1997@gmail.com. Mobile: +62 82146804776.Journal of Health Policy and Management, (2022), 07(02): 149-157https://doi.org/10.26911/thejhpm.2022.07.02.06